الوقف النقدي واستثماره في ماليزيا : خطة مقترحة لتطبيقه في نيجيريا - أديلاني، عبد الكبير بللو (al-Jami'ah al-Islamiyah al-'Alamiyah, 2014)
This thesis focuses and on the study of the application of cash waqf and its investment in institutions of waqf in Malaysia. In the past, cash waqf is among of importance of awqaf issues and its foremost currently because of its many benefits. In the beginning of the research the statement on the search terms. This study provided an opportunity to demonstrate the views of scholars on cash waqf and discuss evidence both permissible and deterrents with the liberalization of the conflict and issues shootout between them. This research exposed and revealed the modern means to invest cash waqf such as: Salam, Murabala, Ijara, istilna, sale-term, and modern means such as: speculation, stocks and bonds, instruments istilna, dwindling participation, Islamic REITs and other investment funds. In addition to this, the researcher explained the contemporary applications of cash waqf in institutions of waqf in Malaysia, such as contributions of cash waqf in institutions of waqf in Malaysia and the direct model of cash waqf in institutions of waqf in Malaysia, Johor Cooperation waqf and International Islamic University Malaysia endowment fund have been chosenas models. This research analyses the investment the modern means for cash waqf in institutions of waqf in Malaysia comparing them with means of investment cited by scholars and its controls. The study relied on inductive approach to the study of objective, analytical approach to analyse the related issues and comparative approach in order to reach the best conclusion. The study continued to several of the most important results: the permissible of Cash Wqaf and the legitimate ways and methods of its investment, applications of cash waqf and its investment in institutions of waqf in Malaysia and the possibility of applying cash waqf and its investment in institutions of waqf in in Nigeria, to reconsider the cash waqf in waqf institution in Zamfara and Kano states of northern Nigeria, and in waqf institution in Oyo state of Southern Nigeria, to introduce the modern means of investment of cash waqf in these institutions, to develop, and to find solutions to the problems of investment of cash waqf. The researcher has taken field work to collect datas and personal interviews with speculation and analysis of all information.